module Roots where
import Data.Complex
import Data.List(genericLength)
roots :: RealFloat a => a -> Int -> [Complex a] -> [Complex a]
roots eps count as =
--
-- List of complex roots of a polynomial
-- a0 + a1*x + a2*x^2...
-- represented by the list as=[a0,a1,a2...]
-- where
-- eps is a desired accuracy
-- count is a maximum count of iterations allowed
-- Require: list 'as' must have at least two elements
-- and the last element must not be zero
roots' eps count as []
where
roots' epr cnt cs xs
| length cs <= 2 = x:xs
| otherwise =
roots' epr cnt (deflate x bs [last cs]) (x:xs)
where
x = laguerre epr cnt as 0
bs = drop 1 $ reverse $ drop 1 cs
deflate z es fs
| es == [] = fs
| otherwise =
deflate z (tail fs) (((head fs)+z*(head es)):es)
laguerre :: RealFloat a => a -> Int -> [Complex a] -> Complex a -> Complex a
laguerre eps count as x
--
-- One of the roots of the polynomial 'as',
-- where
-- eps is a desired accuracy
-- count is a maximum count of iterations allowed
-- x is initial guess of the root
-- This method is due to Laguerre.
--
| count <= 0 = x
| magnitude (x - x') < eps = x'
| otherwise = laguerre eps (count - 1) as x'
where
x' = laguerre2 eps as as' as'' x
as' = polynomial_derivative as
as'' = polynomial_derivative as'
laguerre2 epr bs bs' bs'' y
-- One iteration step
| magnitude b < epr = y
| magnitude gp < magnitude gm =
if gm == 0 then y - 1 else y - n/gm
| otherwise =
if gp == 0 then y - 1 else y - n/gp
where
gp = g + delta
gm = g - delta
g = d/b
delta = sqrt ((n-1)*(n*h - g2))
h = g2 - f/b
b = polynomial_value bs y
d = polynomial_value bs' y
f = polynomial_value bs'' y
g2 = g^(2::Int)
n = genericLength bs
polynomial_value :: Num a => [a] -> a -> a
polynomial_value as x =
--
-- Value of polynomial a0 + a1 x + a2 x^2 ...
-- evaluated for 'x',
-- where 'as' is a list [a0,a1,a2...]
--
foldr (u x) 0 as
where
u y a b = a + b*y
polynomial_derivative :: Num a => [a] -> [a]
polynomial_derivative as
--
-- List of coefficients for derivative of polynomial
-- a0 + a1 x + a2 x^2 ...
--
| as == [] = []
| otherwise = deriv 1 (drop 1 as) []
where
deriv n bs cs
| bs == [] = reverse2 cs
| otherwise = deriv (n+1) (tail bs) ((n*(head bs)):cs)
reverse2 cs
| cs == [] = []
| otherwise = reverse cs
-----------------------------------------------------------------------------
--
-- Copyright:
--
-- (C) 1998 Numeric Quest Inc., All rights reserved
--
-- Email:
--
-- jans@numeric-quest.com
--
-- License:
--
-- GNU General Public License, GPL
--
-----------------------------------------------------------------------------